Optimasi konsentrasi senyawa anti pencokelatan pada penyimpanan jamur kancing (Agaricus bisporus) segar - Suminar Diyah Nugraheni; Harijono Harijono; Agustin Krisna Wardani (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Button mushroom (Agaricus bisporus) is an edible mushroom that has nutritional value and bioactive compounds like β -glukan, unsaturated fatty acids, tocopherol, ergosterol, lectins, polyphenol vitamin D, and selenium that are beneficial for health. The limiting factor of this commodity is its short shelf life, which is 3-4 days after harvest. This research aims to determine the optimum concentration of anti-browning agents (citric acid and EDTA) in the pretreatment process of fresh button mushrooms to obtain the best physical properties (water content, browning index/BI, texture, and weight reduction). The research design uses Response Surface Methodology with Central Composite Design through Design Expert 12 software with a combination of treatment factors are the concentration of citric acid (%) and EDTA (ppm). The results showed that the optimum concentration of citric acid and EDTA was 0.5 % and 100 ppm with the results are 93.63 % for water content, 28.89 % for BI, 23.061 N for texture, and 4.34 % for weight change. This condition is classified as still suitable for consumption.